2014
DOI: 10.1186/2045-3329-4-2
|View full text |Cite
|
Sign up to set email alerts
|

Serum protein acidic and rich in cysteine (SPARC) as a prognostic marker in soft tissue sarcomas

Abstract: BackgroundSerum protein acidic and rich in cysteine (SPARC) is a matricellular secreted glycoprotein that performs several cellular functions and has been implicated in tumorigenesis in a variety of tumor types. The chemotherapeutic agent nanoparticle albumin-encapsulated (NAB)-paclitaxel has been postulated to exploit SPARC expression to target neoplastic cells. SPARC’s role, and potentially the role of NAB-paclitaxel, in the highly heterogeneous class of soft-tissue sarcomas (STS) has not been investigated. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 25 publications
1
5
0
Order By: Relevance
“…Overexpression of serum protein acidic and rich in cysteine (SPARC), a biomarker for albumin bound paclitaxel, was seen in 35.9% of the cases, especially in over 60% of epithelioid hemangioendothelioma (EHE) and chondrosarcoma (notably conventional chondrosarcoma), as well as 48.7% of angiosarcomas. A previous study of SPARC expression by IHC, noted a rate of high SPARC staining in 56% of specimens, but given the small sample size ( n = 27), specific histology correlations could not be made [ 12 ]. Low MGMT expression, a temozolomide associated biomarker, was noted in a variety of sarcomas including alveolar soft part sarcoma (21 ASPS), desmoid, EHE, perivascular epithelioid cell tumor (PEComa), endometrial stromal sarcoma (ESS), giant cell tumor, liposarcoma, LMS, malignant peripheral nerve sheath tumor (MPNST), osteosarcoma and UPS.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Overexpression of serum protein acidic and rich in cysteine (SPARC), a biomarker for albumin bound paclitaxel, was seen in 35.9% of the cases, especially in over 60% of epithelioid hemangioendothelioma (EHE) and chondrosarcoma (notably conventional chondrosarcoma), as well as 48.7% of angiosarcomas. A previous study of SPARC expression by IHC, noted a rate of high SPARC staining in 56% of specimens, but given the small sample size ( n = 27), specific histology correlations could not be made [ 12 ]. Low MGMT expression, a temozolomide associated biomarker, was noted in a variety of sarcomas including alveolar soft part sarcoma (21 ASPS), desmoid, EHE, perivascular epithelioid cell tumor (PEComa), endometrial stromal sarcoma (ESS), giant cell tumor, liposarcoma, LMS, malignant peripheral nerve sheath tumor (MPNST), osteosarcoma and UPS.…”
Section: Resultsmentioning
confidence: 99%
“…Clinically, angiosarcomas and EHE are essentially the only sarcoma subtypes where single agent taxanes are of benefit [ 39 ]. Though, SPARC expression has been assessed in sarcoma specimens, only 1 case of angiosarcoma has previously been evaluated and was found to have high expression of SPARC [ 12 ]. In our study, interestingly, SPARC was overexpressed in angiosarcoma, chondrosarcoma and EHE.…”
Section: Discussionmentioning
confidence: 99%
“…Cyclin D1 expression is induced by mitogens and is crucial for G1 progression[33]. Previous results showed that Smoc2 plays an important role in promoting G1/S progression through participating in the maintenance of cyclin D1 expression[34-36]. In other words, cyclin D1 can be considered as an effector of Smoc2-induced DNA synthesis[37,38].…”
Section: Discussionmentioning
confidence: 99%
“…IHC cutoffs for SPARC have not been established in sarcoma. Previous evaluation of SPARC expression in sarcoma has defined overexpression as a staining intensity of 2+ and percentage of cells stained ranging from 30 to 50 % [ 10 , 12 ]. IHC results in our study were also assessed based upon staining intensity and percentage of cells stained.…”
Section: Methodsmentioning
confidence: 99%
“…SPARC levels did not correlate with specific histologies but did correlate with OS. Low SPARC expressers had a median survival of 22.1 months while in the high expressers, the median survival was 4.4 months [ 10 ].…”
Section: Introductionmentioning
confidence: 99%